Networking in action: Taking collaborative capacity development seriously for disaster risk management - Jenny Iao-Jörgensen (Progress in Disaster Science, 2024)
This study investigates the role of multi-stakeholder networks in disaster risk management (DRM) capacity development and how it aligns with the principles of the Sendai Framework for Disaster Risk Reduction. While the Framework emphasises collaboration, coordination, and partnerships among diverse stakeholders, there remains a gap in understanding how networks foster and sustain collaborative DRM capacity in the context of international development projects. Employing a mixed-method case study approach, this research examines the networking strategies of a Swedish international development project, exploring capacity development outcomes at different levels and early signs of sustainability in three informal networks in Bangladesh, Nepal, and the Philippines. The study focusses on the period one year after the cessation of formal external support. By applying an integrated complex adaptive systems and network governance lens, this study offers a nuanced understanding of the dynamic interplay between various stakeholders and systemic factors influencing network effectiveness to foster and sustain collaborative DRM capacity. The findings enhance our knowledge of informal multi-stakeholder networks in DRM and offer practical insights for optimising institutional designs and networking strategies within and beyond international development projects. The research underscores the importance of scalability, adaptability, and holistic approaches in fostering and sustainable collaborative DRM capacity development. Implications for implementing the Sendai Framework are also discussed.